2022
DOI: 10.1002/aur.2693
|View full text |Cite
|
Sign up to set email alerts
|

Conversational adaptation in children and teens with autism: Differences in talkativeness across contexts

Abstract: Successful social communication is complex; it relies on effectively deploying and continuously revising one's behavior to fit the needs of a given conversation, partner, and context. For example, a skilled conversationalist may instinctively become less talkative with a quiet partner and more talkative with a chattier one. Prior research suggests that behavioral flexibility across social contexts can be a particular challenge for individuals with autism spectrum condition (ASC), and that difficulty adapting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 100 publications
(146 reference statements)
0
6
0
Order By: Relevance
“…Indeed, prior research has suggested that speech and language features produced by conversational partners can be used to predict an autism diagnosis 32,33 . In contrast, ASD participants tend not to adapt their talkativeness based on their partner's behaviour 34 . Together, these data suggest that low diarization precision does not necessarily lead to a poor estimation of the UD of a 15 participant.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, prior research has suggested that speech and language features produced by conversational partners can be used to predict an autism diagnosis 32,33 . In contrast, ASD participants tend not to adapt their talkativeness based on their partner's behaviour 34 . Together, these data suggest that low diarization precision does not necessarily lead to a poor estimation of the UD of a 15 participant.…”
Section: Discussionmentioning
confidence: 91%
“…Audio recordings of each conversation were orthographically transcribed by reliable annotators who were unaware of the participants’ diagnostic status and study hypotheses. Annotators were undergraduate student research assistants, trained on a modified Quick Transcription protocol for XTrans software [ 40 ]; all were trained on segmenting and transcription, with a minimum 92% word-level reliability criteria that must be met consistently before beginning to transcribe ([ 13 , 41 ] for a more detailed description of transcription process). Once a final transcript was created for each participant from the annotators, a graduate researcher removed features from the transcriptions including words or phrases relating to the sex, name, location, and other factors that could be identifying factors.…”
Section: Methodsmentioning
confidence: 99%
“…‘Excessive talking’ is a socially negative behaviour leading to peer rejection (Green et al, 2014; Hoza et al, 2005). It is one of the key symptoms associated with attention-deficit hyperactivity disorder (see Green et al, 2014 for a review) and occurs in certain sub-groups of autistic children (Cola et al, 2022; Nadig et al, 2010) and the elderly (Pushkar et al, 2000; Yin & Peng, 2016). However, it is also a common phenomenon in typically-developing primary-school-age children (Abbot-Smith et al, under revision) and one which has been found to be negatively correlated with working memory and inhibitory control (Blain-Briere et al, 2014).…”
Section: What Do Children Need To Do To Engage With and Maintain A Co...mentioning
confidence: 99%
“…Indeed, among the healthy ageing, excessive verbosity is associated with poor emotion recognition (Ruffman et al, 2010). Without prior knowledge of a conversation partner's interest, it is the real-time rapid interpretation of his or her non-verbal affect which often provides the crucial clue as to whether the speaker should continue talking or not (Cola et al, 2022), in order for the conversation to be a co-operative act (Grice, 1975;Tomasello, 2019). Another relevant finding from the healthy ageing literature is that speakers considered 'overly verbose' tend to have poorer inhibitory control (Pushkar et al, 2000;Yin & Peng, 2016).…”
Section: Key Subcomponents Of Social Conversational Abilitymentioning
confidence: 99%
See 1 more Smart Citation